1998
DOI: 10.1097/00002820-199804000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Information needs, uncertainty, and anxiety in women who had a breast biopsy with benign outcome

Abstract: A retrospective, descriptive study to determine the information needs of women who underwent a breast biopsy with a benign outcome and to ascertain the levels of uncertainty and anxiety they experienced was conducted in two community health care sites in Winnipeg, Manitoba. A sample of 70 women completed a four-part survey after learning the benign breast biopsy diagnosis. The survey consisted of an Information Needs Questionnaire, Mishel Uncertainty in Illness Scale--Community Form, State-Trait Anxiety Invent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
75
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 32 publications
8
75
0
1
Order By: Relevance
“…One possible predictor of expectancies for post-surgical pain and fatigue is pre-surgical distress, often experienced by women awaiting curative as well as diagnostic breast surgery (e.g., Benedict, Williams, & Baron, 1994;Deane & Degner, 1998;Poole, 1997). According to Leventhal's dual process model (Leventhal, Leventhal, & Cameron, 2001), emotional factors can affect cognitive factors.…”
Section: Introductionmentioning
confidence: 99%
“…One possible predictor of expectancies for post-surgical pain and fatigue is pre-surgical distress, often experienced by women awaiting curative as well as diagnostic breast surgery (e.g., Benedict, Williams, & Baron, 1994;Deane & Degner, 1998;Poole, 1997). According to Leventhal's dual process model (Leventhal, Leventhal, & Cameron, 2001), emotional factors can affect cognitive factors.…”
Section: Introductionmentioning
confidence: 99%
“…The rational response to this, to which we are expected to aspire is reduction uncertainty (Bradac 2001). Information and the degree of personal control that it affords is commonly cited as the means by which to reduce that uncertainty (Deane and Degner 1998;Eisinger, Geller et al 1999;Lemaire 2004). The required information, an understanding of disease processes and an established cause-effect relationship, is however rarely available.…”
Section: Uncertainty Managementmentioning
confidence: 99%
“…Although has the lower mortality compared to breast cancer, attention regarding management of this tumor is needed because it can affect the quality of life (QoL) and productivity of the sufferers (Goehring and Morabia, 1997). Pain in the region of the tumor, depressed and anxious feeling about the disease are the factors causing a decrease in the QoL in patients with benign breast tumors (Deane and Degner, 1998). Andrykowski, et al study (1996) showed that patients with breast cancer and benign breast had no different level of psychological stress.…”
Section: Introductionmentioning
confidence: 99%